2013
DOI: 10.1097/igc.0b013e31827c7708
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Wnt7a Is Associated With Tumor Progression and Unfavorable Prognosis in Endometrial Cancer

Abstract: Overexpression of Wnt7a may contribute to the progression of endometrial cancer and thus may serve as a new biomarker to predict the prognosis of endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…In tissues, WNT7A expression was found higher in ovarian cancer compared with normal ovaries and benign tumors [16,38], as well as overexpressed in endometrial cancer compared with normal endometrium and benign endometrial lesion [39].…”
Section: Discussionmentioning
confidence: 98%
“…In tissues, WNT7A expression was found higher in ovarian cancer compared with normal ovaries and benign tumors [16,38], as well as overexpressed in endometrial cancer compared with normal endometrium and benign endometrial lesion [39].…”
Section: Discussionmentioning
confidence: 98%
“…20 It was reported that sFRP expression is reduced by epigenetic inactivation in several cancer types. 21–25 21–25 21–25 21–25 21–25 Until now, there is no study investigating the relationship between sFRP4 SNPs and LC. So, this is the first study in this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Two immunohistochemical studies investigated the expression of ligand WNT7A. The first study found that WNT7A was overexpressed (27), and the second study revealed the decrease in the expression in endometrial cancer (28). We detected a downregulated expression of CTNNB1 and AXIN2 genes in stage I adenocarcinoma samples, but no significant changes in the protein level in most of the patients.…”
Section: Discussionmentioning
confidence: 74%